Dimensi Serat Avicennia marina (Forsk). Vierh and Avicennia alba Blume - Rizalinda, Sulastri, Mukarlina (Universitas Tanjungpura, 2014)
Avicennia marina and Avicennia alba are mangrove plants in mangrove forests of west Kalimantan. Mangrove forests can be economically exploited for exsample, pulp and paper raw materials. The porpose of this study was to determine the fiber dimensions of A.marina and A. alba plants. This study was conducted from November 2012 to January 2013. This study used Schimds maceration metod. The result of the measurement showed that the legths of A.marina and A. albas fiber rod were medium-sized fibers. The range of A. marina was 1185,94 m-1244,64 m and the range of A. alba was between 1130,74 m-1345,48 m. The thickness of A. marinas stem wall ranged from 2,86 m-2,97 m and A.alba ranged from 3,00 m-3,05 m and they were classfied as thin walls. The lumen diamater of A. marina stem ranged from 7,32 m- 8,00 m and A. alba varied from 8,95 m-9,42 m fiber. The fibers of both stems of A. marina and A. alba were relatively narrow lumen diameters. Based on the resuls of the fiber dimension measurement from A. marina, it can be used as a raw material of paper and A. alba can be used as a low quality building materials